2011
DOI: 10.1089/gtmb.2011.0024
|View full text |Cite
|
Sign up to set email alerts
|

Sequence Variation of the Methylene Tetrahydrofolate Reductase Gene (677C>T and 1298 A>C) and Traditional Risk Factors in a South Indian Population

Abstract: Methylene tetrahydrofolate reductase (MTHFR) plays a significant role in the metabolism of methionine. MTHFR deficiency is an autosomal recessive trait that could be a significant risk factor for a number of defects, for example, vascular events, due to lower dietary folate intake among South Indians. To find the incidence of 677 C>T and 1298 A>C in MTHFR gene single nucleotide polymorphisms (SNPs) among the south Indian population, polymerase chain reaction and restriction fragment length polymorphism were em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
9
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 10 publications
1
9
0
Order By: Relevance
“…14 Earlier studies have reported inconsistent results regarding the association between the 677C>T and 1298A>C polymorphisms and congenital cardiac defects. [9][10][11]15 In our previous studies, we failed to demonstrate a relationship between neural tube defects and MTHFR polymorphisms in a Turkish population, despite the high prevalence of the condition. 16 The present study was conducted to evaluate the polymorphisms 677C>T and 1298A>C in a group of Turkish children with various types of congenital heart defects.…”
mentioning
confidence: 90%
See 3 more Smart Citations
“…14 Earlier studies have reported inconsistent results regarding the association between the 677C>T and 1298A>C polymorphisms and congenital cardiac defects. [9][10][11]15 In our previous studies, we failed to demonstrate a relationship between neural tube defects and MTHFR polymorphisms in a Turkish population, despite the high prevalence of the condition. 16 The present study was conducted to evaluate the polymorphisms 677C>T and 1298A>C in a group of Turkish children with various types of congenital heart defects.…”
mentioning
confidence: 90%
“…Earlier studies have reported inconsistent results regarding the association between the 677C>T and 1298A>C polymorphisms and congenital cardiac defects …”
mentioning
confidence: 96%
See 2 more Smart Citations
“…Recently, SNPs have been used as a tool for predicting diseases (12) in addition to carcinogenesis (13,14). The MTHFR gene A1298C polymorphism has been implicated in several diseases (15,16), including various types of cancer (17,18), and has been investigated in relation to the risk of PC but with inconclusive results (19)(20)(21)(22)(23)(24)(25)(26)(27). Among the nine eligible casecontrol studies, three considered the MTHFR gene A1298C polymorphism as a genetic marker for PC (19,24,26), while six reported negative associations between the two (20)(21)(22)(23)25,27).…”
Section: Introductionmentioning
confidence: 99%